KNIGHT SHIFT IN ALKALI METALS IN THE REGION OF THE METAL-NON-METAL TRANSITION - Дудик, Михайло (SWorldJournal, 2023)
The article develops a method for calculating the Knight shift in alkali metals in the region of the metal – non-metal transition, which is based on taking into account the localization processes of conduction electrons on ions during the expansion of met